Hyper IgE Syndrome Associated With Warts: A First Case of Dedicator of Cytokinesis 8 Deficiency in the Philippines - Villanueva, Jose Carlo Miguel M.; Chan, Koon-Wing; Ong, Remedios C.; Andaya, Agnes G.; Lau, Yu-Lung; van Zelm, Menno C.; Kanegane, Hirokazu (Frontiers in Pediatrics, 2020)
Hyper IgE syndrome (HIES) encompasses a group of primary immunodeficiency diseases (PIDs) that is characterized by severe atopy, and recurrent infections and markedly elevated serum IgE levels. The majority of HIES cases suffer from autosomal dominant mutations in the signal transducer and activator of transcription 3 gene. A minority of cases display autosomal recessive inheritance, and one form is caused by mutations in the dedicator of cytokinesis 8 (DOCK8) gene. Here we describe the first recognized and diagnosed case of DOCK8 deficiency in the Philippines. A 14 year-old-girl was referred due to recalcitrant atopic dermatitis, recurrent sinopulmonary infections, with widespread warts on the face, trunk and extremities. She had no coarse facial features or retained primary teeth, whereas she presented with widespread viral skin infections and multiple allergic diseases. Laboratory examinations revealed elevations in eosinophil count and serum IgE. The level of T-cell receptor excision circles was undetectable. The patient was suspected to have HIES with a probable DOCK8 deficiency. Genetic analysis disclosed a large genomic deletion involving exons 2-4 in the DOCK8 gene. A combination of recalcitrant atopic dermatitis, asthma, food allergies, with viral skin infections should increase the physician's consideration of a PID. Patients with HIES accompanied by warts and T-cell deficiency can be strongly suspected to have DOCK8 deficiency.